Broken for you [compact disc, unabridged] - Kallos, Stephanie (Blackstone Audiobooks, 2004)
When we meet septuagenarian Margaret Hughes, she is living alone in a mansion in Seattle with only a massive collection of valuable antiques for company. Enter Wanda Schultz, a young woman with a broken heart who has come to Seattle to search for her wayward boyfriend. Both women are guarding dark secrets and have spent many years building up protective armor against the outside world. But as the two begin their tentative dance of friendship, the armor begins to fall away and Margaret opens her house to the younger woman. This launches a series of remarkable and unanticipated events, leading Margaret to discover a way to redeem her cursed past and Wanda to learn the true purpose of her cross-country journey.